Study the effect of eggs incubation parameter through development of new experimental rig for IKTA quails species - Ramli, Mohd Badli (2017)
Nowadays, machine is utilized as an alternative way to hatch eggs, however various temperature settings are used that result in different percentages of hatching between hatcheries. This study aims to investigate the effect of increasing incubation temperature, eggs movement type, and incubation time through a set of experimental rigs developed specifically to suit the experimental needs to determine the best eggs incubation parameter. Air flow and heat movements were simulated using Computational Fluid Dynamic Simulation and Modelling (CFX) to study the heat flow effect on hatchability before incubation construction. For case study, Institut Kemahiran Ternakan Ayam (IKTA) species used as test subjects. Incubation period took 17 days to completed. Setting temperature in each test run was different in the first day to the 14th and 15th to 17th day. First test run, the setting was 37 °C for 14 days then 38 °C for 3 days. In second incubation, 38 °C on the 14th day and 39 °C for 3 days, then third setting at 39°C on the 14th day and 40 °C for 3 days. Each setting was repeated three times, thus nine test runs were performed. With the same setting incubation temperature and humidity, two types of eggs movement were conducted in the same incubation chamber, 40 eggs were placed in 45 ° swing and 360 ° rolling. Unhatched eggs were opened and examined to see any abnormalities that may cause death of the embryo. From the data collected, temperature 37 °C14day 38 °C3day produced 89.17% eggs hatch, first eggs hatch in day 14 with average 5.42%, ends in day 16. By increasing 1-degree temperature, it decreased hatching to 84.17% with 6.67% hatch in day 14. By increasing 1 degrees, resulted just 76.67% eggs hatch, average 12.91% hatch in day 14. Thus, proved that by increasing temperature to 39°C was not as successful as 37 °C. Excessive temperature did not increase hatchability but speed up hatching time, it may cause embryonic mortality to egg development. Overall, experimental rig produces 83.16% hatching with 360 ° rolling produced slightly higher hatching average at 83.33% compared to 83% with 45° swing.